Dampak Open Door Policy Pada Stabilitas Ekonomi dan Politik Jerman serta Hubungan dengan Uni Eropa - Lutfie, Ratu Zahirah; Opranata, Wanda; Riyadinta, Nanda; Alunaza, Hardi (Jurnal Ranah Publik Indonesia Kontemporer (Rapik), 2024)
During a period when Europe was facing a crisis and several countries were turning away refugees, Germany chose to welcome them and emerged as a key destination for refugees from different countries. The country's decision to adopt the Open Door Policy has had a profound effect on its stability, leading to notable economic and political consequences both within Germany and in its diplomatic relations with the European Union throughout the policy's duration. This study analyzes the stability of Germany’s policy in managing refugees from 2015 to 2022, which was one of its responses to the European refugee crisis with qualitative approach. The policy faced criticism from segments of the German public, particularly opposition party members, and also drew scrutiny from some European Union member states. Moreover, it has had long-term effects on the economic and demographic sectors. Merkel, as Germany’s Chancellor who introduced the policy, was undeterred by criticisms directed at her approach.